2017
DOI: 10.53369/dzwk6998
|View full text |Cite
|
Sign up to set email alerts
|

Breach of Psychological Contract and Quality of Life; Psychosomatic Strain as Mediator and Power Distance as Moderator

Abstract: This study empirically examined the impact of breach of psychological contract on employees’ quality of life via the mediating mechanism of psychosomatic strain, while facilitating effect of power distance was also examined. Data were collected from a sample of 183 employees using a questionnaire. Results confirm that the breach of psychological contract declines employees’ quality of life, while mediating role of psychosomatic strain in this particular relationship was also established. Contrary to expectatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Based on the analysis, it is revealed that a strong, balanced form of exchange relationship or psychological contract has been formed with the employer, thus yielding positive results for the organization in terms of employees being actively engaged in and experiencing a moderate level of stress (Blau, 1964). As suggested by the literature, an unbalanced form of exchange relationship (an instrumental PC) has more negative consequences for the organization, because the employees feel that the organization did not reciprocate in the desired manner and their PC has been breached or violated which ultimately contributes to a high level of strain (Asad, 2017;Gakovic & Tetrick, 2003;Hakanen, Bakker & Shaufeli, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the analysis, it is revealed that a strong, balanced form of exchange relationship or psychological contract has been formed with the employer, thus yielding positive results for the organization in terms of employees being actively engaged in and experiencing a moderate level of stress (Blau, 1964). As suggested by the literature, an unbalanced form of exchange relationship (an instrumental PC) has more negative consequences for the organization, because the employees feel that the organization did not reciprocate in the desired manner and their PC has been breached or violated which ultimately contributes to a high level of strain (Asad, 2017;Gakovic & Tetrick, 2003;Hakanen, Bakker & Shaufeli, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship paradigm has received considerable attention from academics and practitioners in the past several decades. Argyris (1960) first referred to the concept of individual psychological contract to attracting, maintaining, and enhancing individual employees" relationships. Various scholars contributed their views to sets out the employment rights and obligations since the born of social exchange in 1960s (Argyris, 1960;Blau, 1964).…”
Section: Individual Psychological Contract Breachmentioning
confidence: 99%
“…Argyris (1960) first referred to the concept of individual psychological contract to attracting, maintaining, and enhancing individual employees" relationships. Various scholars contributed their views to sets out the employment rights and obligations since the born of social exchange in 1960s (Argyris, 1960;Blau, 1964). Argyris (1960) was the first to use the term individual psychological work contract to define the implicit agreement between employers and their employees.…”
Section: Individual Psychological Contract Breachmentioning
confidence: 99%
See 1 more Smart Citation